GARGLING EXPERIENCE, TRAINING, PROFESSIONALISM, INDEPENDENCE, MOTIVATION TOWARDS THE PERFORMANCE OF INTERNAL AUDITORS ON PT. ALAM JAYA WIRASENTOSA - Liviani; Thomas Sumarsan Goh; Elidawati; Edison Sagala (SEAN Institute, 2022)
Nowadays, the growth of the business is getting faster, resulting in the increasing competition between business industries. Therefore, many business owners are trying to improve their income to be able to survive in the fierce competition in the industries. Using an auditor in the company shows the importance of an auditor in a company. This final project is to aim to see the impact of experience, training, professionalism, independence, and motivation in PT.Alam Jaya Wirasentosa. The research methods used in this final project are quantitative methods. The sample population containing 32 samples are gathered from all the employee working in the audit department from PT. Alam Jaya Wirasentosa, the technique used to gather this sample is using nonprobability sampling. And the analysis data method use to create a hypothesis is multiple regression. The result of this final project shows that experience, training, professionalism, independence and motivation have simultaneously and significantly impacted the auditor performance in PT. Alam Jaya Wirasentosa. Also, the result has shown that experience, training, professionalism, independence and motivation have partially improved the performance of auditors in PT. Alam Jaya Wirasentosa.